Technologies of Brand Development and Positioning - S. B. Baurina (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Market economy develops very fast in current conditions, which fosters the growth in the number of goods and services of one product group. It helps avoid monopoly, but at the same time it makes customer choice more difficult as they get lost in the vast number of similar offers. This problem can be resolved by branding, i. e. proving product with the brand, a set of tangible and intangible values that can identify and differentiate product and impact customer choice. It is the product itself, its trade mark and other visual and physical components, its surrounding halo and relations between the company and the buyer. Successful branding gives an opportunity to get a trusted audience and retain it even in unstable economic conditions and it can prepare the ground for business extension and cut costs in new product and service promotion. Brand development can have a positive impact on investors’ loyalty, financial quarters, workers and mass media, that is why the brand is often perceived as a valuable asset of the company. The article specifies the notion of brand and branding, identifies stages of the brand life cycle and marketing tasks typical of each stage. The first and fundamental stage of brand development is positioning. Positioning is a product place on market. To build positioning tactics it is important to identify the current and desirable position of the brand and develop brand strategy. Varieties of brand positions are shown. The essence of mission, vision and value of brand is revealed. Specificity of brand identification is described: development of outer attributes that personify its individuality (name, slogan, logotype, package, design and company style). Identification can pass on to customer the precise information about the brand notion. Apart from this benefits of branding are shown for different target groups. Findings of the research supplement the existing theoretical and methodological approaches to brand development and positioning in conditions of uncertain business environment.